Transforming a Traditional Library to Modern Library using Barcode Technology: An Experience of Central Library, PEC University of Technology, Chandigarh - Vasishta, Seema; Kaur Dhanda, Maninder (DESIDOC Journal of Library & Information Technology, 2010)
The article appraises the transformation of central Library of PEC University of Technology, Chandigarh into a modern library using barcode technology. Appraisal has been made by comparing the prerequisites and practices of the method used earlier with the prerequisites and practices being followed these days. The benefits incurred by adapting the barcode technology have also been discussed along with the future plans for the Central Library, PEC University of Technology. DOI: 10.14429/djlit.30.284